Justiça organizacional e comportamentos retaliatórios: um estudo com jovens trabalhadores - David Silva Franco (2016)
The objective of this study is to identify and understand the factors that influence perceptions of organizational justice and retaliatory behavior of young participants of the Associação de Ensino Social Profissionalizante. Researches that circumscribe the theories of organizational justice and retaliatory behaviors are emerging in Brazilian scientific literature, being the field of Administration still little explored. These issues involve the perceptions of justice and injustice of individuals in the workplace, as well as the defense strategies that they use when they feel wronged. Such strategies can be presented through retaliatory behavior at work, which are negative reactions of workers against the organization or people who work there. The literature review showed that studies covering those theories are predominantly quantitative, seeking correlations and prominent variables that influence them. However, little research has been addressing the seizure of the reasons shrouded the perceptions of justice and injustice, and the specific factors that stimulate or inhibit the retaliatory behavior. In order to deepen the empirical knowledge and cover part of the identified gap, this research, qualitative, focuses on the subjective aspects of justice and retaliation perceptions, considering the chosen group peculiarities. The scientific literature has shown that young people are an idiosyncratic public and few works have been done with it within the organizational behavior, which indicates the need for research aimed at unveiling its peculiarities. Given their working relations usually fragile, transient and precarious, the young people deserves special attention because they are in a period of adaptation to the professional reality and it is likely to impact on physical and mental health as a result of socio-organizational injustice. With the content analysis of 23 interviews, it was possible to see that the researched group, contrary to what the literature suggests, has perceived the workplace as mostly fair, and the retaliatory behaviors were barely identified. That said, the relevance of this research focuses on the quest for understanding the reasons wrapped on the conformation of the panorama noticed, offering greater reflectivity for studies on such issues and such social actors in organizational behavior field.